1994
DOI: 10.1590/s0074-02761994000400019
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the replication of Mayaro virus grown in interferon treated cells

Abstract: Mayaro virus grown in interferon treated infected cells has been characterized with regard to its ability to replicate in vertebrate (TC7) and invertebrate (Aedes albopictus) cells. Virus purified from interferon treated TC7 cells adsorbs and penetrates to the same extent as the control virus. During infection, these virus particles caused inhibition of host protein synthesis and synthesized the same spectrum of viral proteins as normal virus. This population however, was apparently more sensitive to interfero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…According to Rebello, Fonseca et al (1993) the replication of the MAYV is drastically inhibited by INF activity [33]. However, our study revealed that the challenge performed in cells constitutively expressing shRNA with MAYV did not present differences in the number of plaques formed among cells and controls.…”
Section: Discussionmentioning
confidence: 63%
“…According to Rebello, Fonseca et al (1993) the replication of the MAYV is drastically inhibited by INF activity [33]. However, our study revealed that the challenge performed in cells constitutively expressing shRNA with MAYV did not present differences in the number of plaques formed among cells and controls.…”
Section: Discussionmentioning
confidence: 63%